2015
DOI: 10.1016/j.cell.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity Promotes Glioma Growth through Neuroligin-3 Secretion

Abstract: SUMMARY Active neurons exert a mitogenic effect on normal neural precursor and oligodendroglial precursor cells, the putative cellular origins of high-grade glioma (HGG). By using optogenetic control of cortical neuronal activity in a patient-derived pediatric glioblastoma xenograft model, we demonstrate that active neurons similarly promote HGG proliferation and growth in vivo. Conditioned medium from optogenetically stimulated cortical slices promoted proliferation of pediatric and adult patient-derived HGG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
573
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 644 publications
(651 citation statements)
references
References 81 publications
21
573
0
Order By: Relevance
“…Conditioned medium (CM) from optogenetically-stimulated acute cortical slices from Nlgn3 WT or KO; Thy1::ChR2 mice demonstrated that the increase in glioma cell proliferation induced by active CM is incompletely abrogated in the context of Nlgn3 KO (Extended Data Fig. 2a), replicating the degree of differential proliferation previously accounted for by activity-regulated Bdnf 1 . Taken together, these findings indicate that glioma growth is more dependent on neuroligin-3 in vivo than would have been predicted from these in situ / in vitro experiments.…”
supporting
confidence: 64%
See 4 more Smart Citations
“…Conditioned medium (CM) from optogenetically-stimulated acute cortical slices from Nlgn3 WT or KO; Thy1::ChR2 mice demonstrated that the increase in glioma cell proliferation induced by active CM is incompletely abrogated in the context of Nlgn3 KO (Extended Data Fig. 2a), replicating the degree of differential proliferation previously accounted for by activity-regulated Bdnf 1 . Taken together, these findings indicate that glioma growth is more dependent on neuroligin-3 in vivo than would have been predicted from these in situ / in vitro experiments.…”
supporting
confidence: 64%
“…We found no effect of NLGN1, NLGN4X/Y (Extended Data Fig. 2b,c) or NLGN2 1 on glioma proliferation. Thus, compensatory expression of other neuroligins would not be expected to influence glioma growth, supporting a unique role for NLGN3 in glioma pathobiology.…”
mentioning
confidence: 60%
See 3 more Smart Citations